Supporting self-regulated learning in primary education: insights from a Montessori classroom - Kersna, Liina; Lepp, Liina; Pedaste, Margus; Laak, Kristjan-Julius (Frontiers in Education, 2025)
Self-regulated learning is a key component of Maria Montessori’s pedagogy, which emphasizes the importance of children managing their own learning process. Several studies confirm that children attending Montessori preschool and school exhibit better self-regulated learning (SRL) skills, but there is less research on what makes the Montessori classroom environment one where students’ SRL skills can develop. The aim of this qualitative case study was to identify the characteristics that support SRL in the Montessori classroom based on descriptions provided by Montessori teachers and observations of a Montessori primary classroom. The case study sample included students (N = 18) aged 6–10 from a Montessori-based school’s primary learning group and their teachers (N = 2). During the study, the work of the Montessori learning group was observed over the course of one school week, totalling 14 h. Semi-structured interviews were conducted with the teachers before and after the classroom observations. The data were analysed using qualitative content analysis, combining both inductive and deductive content analysis methods. The results show that in the Montessori classroom, learners had several choices regarding what, when, with whom, how, and where they learned, and they had the opportunity to control their learning process, deciding how thoroughly and at what pace they engaged with the chosen task. In addition, learners had the opportunity to solve open-ended tasks and take breaks at appropriate times. Collaboration among students was encouraged in the classroom, and students were given the opportunity to evaluate both their own and their peers’ work. Montessori teachers also provided instrumental support to learners, helping them make appropriate choices in their learning and encouraging them to dedicate themselves more thoroughly to the topics they had chosen. The teachers used evaluation practices that supported learning, emphasizing the learner’s personal development and goals. The characteristics of a high-SRL classroom were evident in the Montessori classroom.